Orientation-dependent nanostructure arrays based on anisotropic silicon wet-etching for repeatable surface-enhanced Raman scattering. Issue 8 (8th February 2016) - Wang, C. G.; Wu, X. Z.; Di, D.; Dong, P. T.; Xiao, R.; Wang, S. Q.
Abstract : A new class of orientation-dependent metallic NS arrays is successfully fabricated based on the combination of the NSL technique and the anisotropic wet etching process, and gives stable, sensitive and reproducible SERS responses. Abstract : Repeatable fabrication of sensitive plasmonic substrates through a simple procedure has become a major challenge for SERS-based sensing and imaging. Herein, a new class of high-performance SERS substrates, including pyramid, ridged-hexagon, and quasi-triangle nanostructures, is successfully fabricated based on the nanosphere lithography technique and anisotropic wet etching. Using the wafer-scale Cr-hole array as the etching mask, cavity-templates of various configurations are fabricated by the orientation-dependent wet etching technique, from where the nanostructure arrays are finally peeled-off. The anisotropic wet etching on (100), (110), and (111) silicon wafers has been systematically studied at the nanoscale revealing the formation mechanism of these cavity-templates. The peeled-off nanostructure arrays provide high-density tips and/or gaps (about 2.5 × 10 7 mm −2 ) and thus facilitate the generation of "hot spots". The distribution of the electromagnetic field is visualized by the finite difference time domain calculation. And the calculation results are validated by SERS characterization. The SERS enhancement factors of these substrates are in the order of 10 6 –10 7, with the maximum enhancement factor of 1.32 × 10 7 yielded by the ridged-hexagon arrays. The proposed nanostructure arrays present excellent homogeneity and reproducibility (with the largest relative standard deviation of 16.43%) for the reason that the SERS-active substrates are peeled-off from an identical template. The cost-effective fabrication, high sensitivity, good homogeneity and well-performed reproducibility demonstrate that these orientation-dependent NSs are good candidates for SERS-based in vitro and in situ detection and biosensing.